Teachers Identified Challenges to Implement Differentiated Instruction in Mainstream Primary School Mathematics Classrooms - Maphumulo, Thabisile; Biccard, Piera (Universitas Negeri Semarang, 2024)
Differentiated instruction is finding more grounding and impact in education around the world. As classroom diversity is anticipated and welcomed, teachers need to implement differentiation practices as part of their usual practices. However, this is known to be a more challenging task than first thought, with the challenges that teachers face being interrelated and complex. In this study, the researchers focus on twelve rural and peri-urban primary school mathematics teachers and two district officials, their identified challenges in implementing and practicing differentiated instruction. The research was qualitative in nature. Teachers participated in semi-structured individual interviews and focus group interviews. The researchers use the framework of differentiated instruction across content, processes, product, and environment to frame teachers' responses regarding their experiences with differentiation. Teachers indicated that challenges occurred in four broad areas: time, resources, overcrowded classrooms, and parental support, suggesting the need for further professional development in this area. The researchers recommend that differentiated instruction is not viewed as a special instance of teaching, but that all teaching take on a differentiated nature in keeping with teaching for excellence and inclusivity.